2021
DOI: 10.1007/s40820-021-00769-2
|View full text |Cite
|
Sign up to set email alerts
|

High-Index Faceted Nanocrystals as Highly Efficient Bifunctional Electrocatalysts for High-Performance Lithium–Sulfur Batteries

Abstract: Precisely regulating of the surface structure of crystalline materials to improve their catalytic activity for lithium polysulfides is urgently needed for high-performance lithium–sulfur (Li–S) batteries. Herein, high-index faceted iron oxide (Fe2O3) nanocrystals anchored on reduced graphene oxide are developed as highly efficient bifunctional electrocatalysts, effectively improving the electrochemical performance of Li–S batteries. The theoretical and experimental results all indicate that high-index Fe2O3 cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 65 publications
(110 reference statements)
0
33
0
1
Order By: Relevance
“…Considering that the particular crystal facet of nanocatalysts might harness the selective electrocatalytic activity for accelerating the specific reaction step in Li–S batteries, the rational adjustment of crystal facet exposure offers an appealing solution to realize bidirectional polysulfide electrocatalysis. [ 141 ] In this sense, Yu et al. designed VO 2 with highly exposed (110) and (002) facets (denoted as (110)VO 2 and (002)VO 2 , respectively) to probe the facet effect for catalyzing bidirectional Li–S chemistry.…”
Section: Heterogeneous Electrocatalystmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the particular crystal facet of nanocatalysts might harness the selective electrocatalytic activity for accelerating the specific reaction step in Li–S batteries, the rational adjustment of crystal facet exposure offers an appealing solution to realize bidirectional polysulfide electrocatalysis. [ 141 ] In this sense, Yu et al. designed VO 2 with highly exposed (110) and (002) facets (denoted as (110)VO 2 and (002)VO 2 , respectively) to probe the facet effect for catalyzing bidirectional Li–S chemistry.…”
Section: Heterogeneous Electrocatalystmentioning
confidence: 99%
“…Considering that the particular crystal facet of nanocatalysts might harness the selective electrocatalytic activity for accelerating the specific reaction step in Li-S batteries, the rational adjustment of crystal facet exposure offers an appealing solution to realize bidirectional polysulfide electrocatalysis. [141] In this sense, Yu et al designed VO 2 with highly exposed ( 110) and (002) facets (denoted as (110)VO 2 and (002)VO 2 , respectively) to probe the facet effect for catalyzing bidirectional Li-S chemistry. [142] To begin with, the cyclic voltammetry (CV) profile of sulfur cathode with (110)VO 2 additive exhibits higher current response and lower potential difference as compared to that of (002)VO 2 -mediated electrode, which is indicative of the reduced reaction polarization and elevated redox kinetics (Figure 6a).…”
Section: Facet Engineeringmentioning
confidence: 99%
“…In addition, researchers found that excessive adsorption will give rise to the decomposition of LiPSs and thus hinder the electrochemical redox reactions [ 17 19 ]. Recently, catalytic effect has been recognized as the key technology to improve conversion kinetics and inhibit the shuttle effect simultaneously [ 20 , 21 ]. The conversion of sulfur species is accelerated and thus the shuttle effect is mitigated [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…That is, one component is for LiPS capture and the other is for catalyzing LiPS conversion. 16,17 Over the past few years, researchers have proposed some catalysts as the substrate in sulfur cathodes 18–20 or polypropylene (PP) separators 21–23 so as to accelerate the liquid–solid conversion kinetics, materials such as metal oxides, 24–26 metal sulfides, 21,27 metal nitrides 20,28 and metal selenides. 29,30 Manganic oxides have been proven to strongly adsorb LiPS, both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%